Salivary duct carcinoma of parotid gland with femur metastasis: Case report and literature review - Pantelas Georgios; Salloumis Marios; Myrto Solomou Maria; Gkinosati Angeliki Anna; Georgiou Giorgos; Lillis Markos (Balkan Stomatological Society, 2024)
Histologically similar to both in situ and invasive ductal carcinoma of the breast, salivary duct carcinoma (SDC) is an uncommon and excessively aggressive subtype of primary salivary gland carcinoma. The salivary gland most frequently involved in cancer cases is the parotid. With an estimated frequency of 1 in 1,000,000 individuals, SDC is an incredibly rare cancer that is more common in men. Due of its early metastasis to distant areas and regional lymph nodes, it is frequently identified at an advanced stage. Case report: We present a case of SDC of the parotid gland with femur bone metastasis as well as a detailed literature review for SDC. According to the existing literature, this is the first reported case of salivary duct carcinoma of the parotid gland with femur metastasis. Currently the patient remains stable with no signs or symptoms of recurrence. Conclusions: It is crucial to note the possibility of femur metastasis from salivary duct carcinoma of the parotid gland for the most appropriate treatment plan determination, and a more comprehensive understanding of the disease's progression.